Underdiagnosis of frontotemporal lobar degeneration in Brazil - Bahia,Valéria Santoro (2007)
Abstract Frontotemporal lobar degeneration (FTLD) is a progressive neurodegenerative disorder that involves the frontal and anterior temporal lobes. It is characterized by prominent behavioral and language disorders. There are three variants of FTLD: frontotemporal dementia (FTD), semantic dementia (SD) and progressive non-fluent aphasia (PNFA). FTLD may be mistaken for AD (Alzheimer's disease) or psychiatric disorders especially in the early stages. Objectives: To describe the demographic characteristics of patients with FTLD, assessed at the Behavioral and Cognitive Neurology Unit, and to show that FTLD is commonly clinically under-diagnosed. Methods: All patients diagnosed with FTLD (Consensus Criteria for FTLD), and who were seen at the Behavioral and Cognitive Neurology Unit of Hospital das Clínicas, in São Paulo, Brazil from January 2004 to August 2007 were included in the analyses. Results: Sixteen patients with FTLD (11 women) were included in this study. There were 12 patients with FTD, two with PNFA and two with SD. The mean duration of the illness until diagnosis of FTLD was 4.1±2.3 years, ranging from one to seven years. Nine patients had been initially seen by psychiatrists, five by neurologists, and two by general physicians. The first diagnosis was psychiatric disorder in six patients, AD in four, dementia in two, FTD in two, and stroke and hydrocephalus for one patient each. Conclusion: The diagnosis of FTLD can be difficult and many patients may be misdiagnosed in Brazil, especially in the initial stages. Educational programs on FTLD for the medical community are warranted.